Feeding Behavior of Lactating Dairy Cattle Fed Sorghum-Based Diets and Increasing Levels of Tannic Acid - José Danrley Cavalcante dos Santos; Edilson Paes Saraiva; Severino Gonzaga Neto; Carla Aparecida Soares Saraiva; Antônio da Costa Pinheiro; Vinícius de França Carvalho Fonsêca; Severino Guilherme Caetano Gonçalves dos Santos; Carla Giselly de Souza; Maria Elivânia Vieira Almeida; Tarsys Noan Silva Veríssimo; Larissa Kellen da Cunha Morais (Agriculture, 2021)
Tannins have been used to trigger positive effects on ruminal metabolism and increase ruminant production efficiency, since they increase the supply of dietary protein in the small intestine. Increasing levels of tannic acid in a sorghum-based diet on the feeding behavior of five Holstein/Zebu crossbred lactating dairy cows was evaluated. They were subjected to a 5 × 5 Latin square experimental design, with fivelevels of tannin as dry matter (DM) in the diet (0.46, 1.30, 2.60, 3.90, and 5.20%). The levels of the tannic acid added were established based on the quantity of condensed tannin in high-tannin sorghum. Thus, diets 2, 3, 4 and 5 were supplemented with 1.5 g (13% DM), 79.5 g (2.6% DM), 157.5 g (3.9% DM), and 235.5 g (5.2% DM) of tannic acid, totaling 0.078, 0.156, 0.234, and 0.321 kg of tannin/day, respectively. Feeding behavior variables included the following states and events: feeding, drinking, rumination, and inactivity; the frequency of visiting the feed and water troughs; and the occurrence of urination and defecation. Water was provided ad libitum, and its intake was measured during periods of behavioral data collection. The use of two tannin sources (hydrolysable and condensed) corresponding to the total level of 5.20% (on a DM basis) in the diet of lactating dairy cattle does not affect the animals’ health. Tannic acid can be included in the diet of lactating dairy cattle at a level of 3.93% (on a DM basis) without inducing variation in the total time spent daily on feed intake. Dairy cows dilute the effects of dietary tannin (5.20%) through greater fragmentation of food consumption in the hours following its supply (180 min). The astringent effects caused by tannin intake in lactating dairy cows are mitigated by increasing the daily water intake as the amount of tannin in the diet increases, starting at a level of 3.90% tannin (on a DM basis).